Mogroside IIIE Alleviates High Glucose-Induced Inflammation, Oxidative Stress and Apoptosis of Podocytes by the Activation of AMPK/SIRT1 Signaling Pathway - Xue W; Mao J; Chen Q; Ling W; Sun Y (Diabetes, Metabolic Syndrome and Obesity, 2020)
Wei Xue,1 Juhua Mao,2 Qingjie Chen,1 Weide Ling,1 Yuqi Sun3 1Department of Pharmacy, Ruikang Hospital Affiliated to Guangxi University of Chinese Medicine, Nanning, Guangxi 530011, People’s Republic of China; 2Center for Drug Control, Lishui Institute for Quality Inspection and Testing, Lishui, Zhejiang 323000, People’s Republic of China; 3Department of Anesthesiology, Guangzhou 12th People’s Hospital, Guangzhou, Guangdong 510620, People’s Republic of ChinaCorrespondence: Yuqi SunGuangzhou 12th People’s Hospital, No. 1 Tianqiang Road, Tianhe District, Guangzhou, Guangdong 510620, People’s Republic of ChinaEmail yuqisunhh@163.comBackground: Diabetic nephropathy (DN) is the leading cause of impaired renal function. The purpose of this study was to investigate the effects of Mogroside IIIE (MG IIIE), a cucurbitane-type compound isolated from Siraitia grosvenorii, in high glucose (HG)-induced podocytes and the possible mechanisms.Methods: MPC-5 cells were cultured under normal glucose or HG conditions. After treatment with MG IIIE, cell viability was examined using a cell counting kit-8 assay. The contents of inflammatory factors and oxidative stress-related markers were determined using the corresponding kits. Additionally, apoptosis of MPC-5 cells was determined using flow cytometry assay and the levels of apoptosis-associated proteins were evaluated by Western blot analysis. Moreover, the expression of proteins in AMPK/SIRT1 signaling was tested and the compound C, an AMPK inhibitor, was used to study whether the effects of MG IIIE on HG-induced MPC-5 cells were mediated by activation of the AMPK/SIRT1 signaling pathway.Results: MG IIIE elevated the cell viability of HG-induced MPC-5 cells, reduced the concentrations of inflammatory cytokines and decreased the levels of oxidative stress-related markers. What’s more, the apoptosis of podocytes induced by HG was inhibited after MG IIIE intervention, accompanied by the upregulated expression of Bcl-2 and downregulated expression of Bax, cleaved caspase-3 and cleaved caspase-9. It was also found that MG IIIE could activate the AMPK/SIRT1 signaling, but compound C inhibited this pathway and reversed the inhibitory effects of MG IIIE on inflammation, oxidative stress and apoptosis in HG-stimulated podocytes.Conclusion: MG IIIE can alleviate HG-induced inflammation and oxidative stress of podocytes by the activation of AMPK-SIRT1 signaling.Keywords: podocytes, inflammation, oxidative stress, apoptosis, AMPK